Ring-based efficient batch authentication and group key agreement protocol with anonymity in Internet of vehicles - Haibo ZHANG; Kai LAN; Zhou CHEN; Ruyan WANG; Can ZOU; Mingyue WANG (Tongxin xuebao)
Aiming at the problem that the current batch authentication and key agreement protocol were relied on semi-trusted road side unit (RSU) and were not suitable for key update in large-scale Internet of vehicles (IoV), a ring-based efficient batch authentication and group key agreement protocol with anonymity in IoV was proposed.The anonymity was ensured by the pseudonym mechanism.The authentication key pairs were constructed by the chaotic map, and the batch authentication for many vehicles was quickly completed by a small number of bilinear maps.The joining and leaving of vehicles in large-scale IoV scenario were fully considered, a ring session group was efficiently constructed by using the semi-group property of chaotic maps, and a group key establishment and update mechanism suitable for large-scale vehicles was designed.In addition, a pseudonym update mechanism and an anonymous tracing mechanism were designed to ensure a more secure session process.At the same time, the BAN logic model was used to prove the semantic security of the protocol.The security analysis and simulation results show that the proposed protocol has multiple security attributes and certain efficiency advantages.